Activated Carbon from Plantain Stems as NO2ˉ and Mn2+ Adsorbent on Well Water - Betsy Felita; Cucun Alep Riyanto; Yohanes Martono (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2021)
Waste contamination in the environment can not be avoided in water, even though water is the main necessity for living things. Contaminants that are too high such as nitrites and manganese will have a negative impact if consumed continuously. In this research, the synthesis of activated carbon from Plantain stems as an adsorbent for nitrite (NO2ˉ) and manganese (Mn2+)contaminants has been carried out. Synthesis of activated carbon from Plantain stem (ACPS) was carried out with a carbon: H3PO4 impregnation ratio of 1:6 (w/w) and heating using a furnace at 600 oC for an hour. Characterization of ACPS using an Infrared Spectrophotometer showed the presence of functional groups C-H, C = H, C≡C, C-O, P-O, and C-NH3+ or P-H bonds. The results of characterization by XRD showed that the ACPS was amorphous but little crystalline. In the adsorption study, the adsorption isotherms of ACPS on NO2ˉ and Mn2+ ions followed the Redlich-Peterson isotherm with R2 values of 0.9968 and 0.4753, respectively. The adsorption kinetics of ACPS on NO2ˉ and Mn2+ ions followed the Diffusion Intraparticle model with R2 values of 0.8585 for NO2ˉ ions and Pseudo Second Order with R2 values of 0.9482 for Mn2+ ions. In the study of the adsorption efficiency of NO2ˉ and Mn2+ ions using ACPS on well water in the Guyangan Jepara villages, it was found that the reduction efficiency was 15%, only at NO2ˉ ion levels.